PENGARUH MOTIVASI BELAJAR DALAM PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA MAN 1 PULANG PISAU - Jamiatul Hamidah; Oktaviani Oktaviani (Program Studi PGSD Universitas Flores, 2023)
Components that influence student learning success are those that originate within students (interest and motivation) and from outside students such as the environment, social, teacher learning methods, and so on. Interest in learning Indonesian at MAN 1 Pulang Pisau is categorized as low due to a lack of student learning motivation, so there are still many low grades. Even though this school is one of the favorite schools with a large enough number of students because it is the only Islamic-based school and has been accredited A. The purpose of this study is to describe how motivation influences learning on student learning outcomes of MAN 1 Pulang Pisau, by applying differentiated learning designed by the teacher Indonesian. This research method is descriptive qualitative method. The population in this study were all students of class X and the sample in the study was class X IPS II MAN I Pulang Pisau. Data collection techniques were carried out by observing learning in class and distributing questionnaires. The data taken is the result of student learning in the form of written tests and questionnaire results which are distributed in the form of a questionnaire. Then the data is described descriptively and a final conclusion is drawn. Based on the results of the study, students' learning motivation in differentiated learning can improve student learning outcomes. Students are more active and enthusiastic in participating in learning, more confident, and able to respect others.